Nowadays, the availability of wind turbines usually approaches the 98%. The objective is to increase the turbines availability, by improving the wind turbine reliability especially for offshore plants. The wind turbines reliability is a pivotal factor in - Botsaris, Pantelis N; Konstantinidis, E.I; Pitsa, D. (Journal of Applied Engineering Science, 2012)
Nowadays, the availability of wind turbines usually approaches the 98%. The objective is to increase the turbines availability, by improving the wind turbine reliability especially for offshore plants. The wind turbines reliability is a pivotal factor in the successfully function of a wind power plant. High reliability can be achieved by understanding and minimizing the failures of the system. Maintenance planning could make maintenance more efficient and could lead to a reduction of failure events. In order to decide the most effective maintenance strategy, it should be identified the most critical components of the wind turbines, which are prone to failures.  The maintenance strategy should take into both the reliability improvement and the reduction of maintenance cost. Moreover, it is essential to determine and record the main cause that provokes the failure event. The data logging and statistical processing of failure information could improve the reliability of the system components. A wind turbine is a complex power generating system consisting of several structural, electrical and mechanical components. Its efficiency depends largely on its reliability level.In the present study, the factors that affect the reliability of a wind turbine are presented, as well as the analytical way of calculating its reliability. The reliability analysis of the wind turbine is based on the systemic approach of the wind turbine subsystems, as its total reliability depends directly on the reliability of the subsystems. Moreover, it is based on a technical analysis of the reliability of complex systems. The model used is the Fault Tree Analysis (FTA), which is an identification method for probable causes of system failure. The relation of reliability, maintainability and availability is also presented and explained by the example of a small wind farm.
Keywords: Wind Turbines; Systems; reliable; Plants; maintenance; FAILURE; availability